The Implementation of Learning Facilities and Infrastructure Management in Improving the Quality of Education at Madrasah Aliyah Islamic Centre (MAIC) Cirebon - Taqiyuddin, Taqiyuddin; Salim, Nur; Indriyanah, Ayu (IAIN Syekh Nurjati Cirebon, 2025)
Quality issues are closely related to the educational process. To create a quality educational process, support from various educational components is needed, including learning facilities and infrastructure. However, in reality, many madrasahs still have limited facilities, so proper management of learning infrastructure is needed to ensure optimal use. This research aims to describe the implementation of learning facilities and infrastructure management and its impact on the improvement of education quality at Madrasah Aliyah Islamic Centre (MAIC) Cirebon. The main issue raised is the limited facilities and the suboptimal utilization of resources by educators and students. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The main informants consist of the head of the madrasa, teachers, administrative staff, and students. The research results show: (1) perseveration of learning facilities at MAIC is generally adequate but not optimally utilized, such as the library and laboratory; (2) The quality of education is influenced by the professionalism of teachers and the completeness elevated screened supporting facilities; (3) Good management of facilities helpless facilities plays Thus, effective management of facilities and infrastructure significantly contributes to the improvement of the quality of education in madrasahs